Output-Based Aid in Mozambique : Private Electricity Operator Connects Rural Households - Cockburn, Mark; Low, Caroline (World Bank, Washington, DC, 2012)
Mozambique's first privately operated concession to generate, distribute, and sell electricity is now up and running in a rural area of Inhambane Province isolated from the country's main transmission grid. The contract was won through competitive bidding by a Mozambican and South African consortium and leaves the private operator free to develop the power system in the concession area in the way most cost-effective. Designed to tackle the extremely low levels of connectivity, the concession uses output-based aid subsidies to close the gap between what new infrastructure costs and what households are willing and able to contribute. Payment of the subsidies, made available through an International Development Association credit, is contingent on physical verification of households being connected. Encouraged by early success with the concession arrangement, the government is identifying areas for similar schemes.